Effects of Emotion Regulation Training on Attachment Style of Primiparous Pregnant Women with Insecure Attachment - Tayebeh Reyhani; Aliye Shojafar; Morteza Modares Gharavi; Saeed Vaghee; Toktam Kazemeini; Shadi Shayan (Mashhad University of Medical Sciences, 2016)
Background: Pregnant women with insecure attachment style are at high risk of psychiatric disorders. Since emotions are the first coordinators of attachment behavior, emotion regulation training can alter maternal attachment style. In this study, we aimed to evaluate the effects of emotion regulation training on the attachment styles of primiparous pregnant women with insecure attachment style. Aim: This study aimed to evaluate the effects of training programs on the headache of patients after spinal anesthesia. Method: This randomized, clinical trial on 40 primiparous pregnant women with age range of 30-34 years, who were referred to healthcare centers of Mashhad, Iran, during 2014. The data collection instrument was Revised Adult Attachment Scale (RAAS). The participants were assigned to intervention and control groups. A training program was implemented on emotion regulation based on dialectical behavior therapy (DBT) for the intervention group. After delivery, RAAS was completed by the mothers again. The control group only received the routine care. To analyze the data, Chi-square and independent t-test were run using SPSS, version 15. Results: Mean ages of the mothers in the intervention and control groups were 26.9±4.04 and 27.5±3.5 years, respectively. According to the results of independent t-test, the difference between the groups was non-significant (P=0.77). The groups were analogous in terms of attachment style pre-intervention. After the intervention, independent t-test did not reflect any significant differences between the groups regarding avoidant (P=0.37) and anxious (P=0.11) attachment styles. However, mean score for secure attachment style was significantly enhanced (P=0.01). Implications for Practice: Our findings revealed that implementation of emotion regulation training increased secure attachment scores. Thus, implementing emotion regulation training program is recommended as part of a program for pre-natal care in healthcare centers.